Molecular orientation dependent divergence into electro-chemical sensing performance of Pd decorated ZnO nanosheets during guanine adsorption: A comparative analysis - Maity Indranil; Hazra Subhradeep; Majumdar Aheli (EPJ Web of Conferences)
In the present study the variation of different electro-chemical properties was compared, such as the molecular electrostatic potential (MEP), the highest occupied molecular orbital (HOMO), and the lowest unoccupied molecular orbital (LUMO), for the sensing of guanine molecule on palladium (Pd) doped ZnO nanosheet, in four different orientations, through first principle-based computations in Gaussian 09W and GaussView 6.0 software. After structural optimizations, the guanine molecule was observed over the Pd-doped ZnO nanosheet in four different orientations (with tilt angles), parallel to the ZnO nanosheet horizontal plane. It was found that in System-A (first case), the guanine molecule was nearly tilted by 10˚, with an adsorption energy of -0.257 eV, and binding distance of 3.33 Å, for System-B (second case), the same guanine molecule was tilted by almost 50˚ with an adsorption energy of -0.425 eV, and binding distance of 2.29 Å, whereas for System-C (third case) and System-D (fourth case), the adsorption energy, binding distance, and tilt angle was -0.402 eV, 2.29 Å, 120˚, and -0.282 eV, 2.37 Å, 150˚, respectively over Pd-doped ZnO nanosheet sensing element.